2014
DOI: 10.2298/aci1401113k
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic protocol in the treatment of hypo functional kidney

Abstract: Laparoscopic nephrectomy is indicated in the treatment of many benign conditions of the kidneys. Hydronephrosis caused by obstruction of the ureter, either internal, or external, is one of the main indications for laparoscopic reconstruction. If an obstruction is prolonged, consequently, it leads to chronic inflammatory process accompanied by persistent and recurrent pain with fever, which eventually become resistant to therapy. If not operated sufficiently fast to resolve the causes, as a consequence it leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…At present, the major causes for kidney resection are still benign kidney diseases ( 9 ). Rassweleir et al ( 3 ) reported that in a series of 482 nephrectomy operations, 92% were due to benign kidney diseases.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the major causes for kidney resection are still benign kidney diseases ( 9 ). Rassweleir et al ( 3 ) reported that in a series of 482 nephrectomy operations, 92% were due to benign kidney diseases.…”
Section: Discussionmentioning
confidence: 99%